ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN BRIZZI BANK RAKYAT INDONESIA DI KOTA PEKANBARU - Yulia Margaretha Manullang; Anthony Mayes; Yusni Maulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was in order to know the factors that affect Brizzi's demand and to know which factors are the most dominant in influencing Brizzi's demand. Conducted at PT. Bank BRI Pusat Jalan Jendral Sudirman Pekanbaru City Riau Province. Where the population is customers in PT. Bank BRI Pusat Pekanbaru which amounted to 104 people. The sample used in this research is 104 people taken with census method and data processing using multiple linear regression method with SPSS program. Based on the results of the test if the data by using multiple linear regression can be taken several conclusions, namely: Based on the results of a quantitative descriptive test note that one of the factors that influence the use of Brizzi is income. Revenue is positively related to the use of Brizzi. So it can be concluded that the higher the income a person will be the more often he uses Brizzi, Benefits Brizzi positively related to the use of brizzi. So it can be concluded that the more benefits of the brizzi itself, the more people will use brizzi, the ease is positively related to the use of brizzi. So it can be concluded that the easier the brizzi is used it will be more and more people use the brizzi, Revenue is the most dominant factor affecting the use of brizzi, Publishing brizzi relationship with monetary policy is that if more people use brizzi then the money supply will be less reducing inflation then the economy will increase.Keyword : Earnings, Benefits, Convenience, And Use of Brizzi